Tourism development revisited : concepts, issues and paradigms - S, Sutheeshna Babu. (Response Books, 2015)
This book contains a collection of articles by leading experts in international tourism. It broadly covers the tourism business as well as the development of tourism. It documents the different views and paradigms on tourism development in an in-depth manner. In addition to discussing the concepts, scope and nature of the tourism business, the book includes a diverse commentary on: The development of tourism in the 21st century; Emerging models in international tourism; Challenges faced in emerging markets of East Europe, India and China; Impact of Internet and online markets on the travel industry; Changing human resource practices and contributions by the informal sector; The importance of tourism as a source of economic development; The dynamics of the global tourist and corporate traveller; Ecotourism, exotic destinations and experiential tourism; Fundamental issues in leisure, recreation and tourism This book endeavours to a critical approach within a multi-disciplinary framework to relook at the complex phenomenon of tourism development. The unusual intellectual freedom of the scholars is clearly demonstrated throughout this book. It deals with the details in the conceptual and paradigmatic evolution of tourism as a socio-economic phenomenon and an industry, contradictions in its development process, tourism in developing world including the fast-growing Chinese and Indian economies, new tourism products and their development and management.